2008
DOI: 10.1007/s00216-008-2208-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of amide herbicides in environmental water samples with dispersive liquid–liquid microextraction prior to gas chromatography–mass spectrometry

Abstract: This paper describes a novel, simple and environmentally friendly method for rapid determination of the amide herbicides metoalchlor, acetochlor, and butachlor. It is based on dispersive liquid-liquid microextraction and gas chromatography-mass spectrometry. Factors that may influence the enrichment efficiency, such as type and volume of extraction solvent, type and volume of dispersive solvent, extraction time, and content of NaCl, were investigated and optimized in detail. Under the optimum conditions, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Since the DLLME conditions had been optimized in our previous research [24], those results were used in this work. Only the SPE conditions together with some notable parameters in the SPE -DLLME combination were studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the DLLME conditions had been optimized in our previous research [24], those results were used in this work. Only the SPE conditions together with some notable parameters in the SPE -DLLME combination were studied.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that, among the three solvents methanol, acetonitrile, and acetone, acetone can achieve the highest enrichment factors [24]. At the same time, this solvent has advantages such as lower toxicity, lower cost, and so on.…”
Section: Influence Of Solvent Type and Elution Volumementioning
confidence: 98%
“…The method has the obvious advantages of high recovery and enrichment factor, simplicity, rapidness, and low cost [8,9]. It has been widely applied for the enrichment and determination of environmental pollutants in environmental samples [8][9][10][11][12][13][14][15]. DLPME has obtained great attention from the sample pretreatment researchers because of its obvious advantages, but has the demerit of using toxic organic solvents in the microextraction.…”
Section: Introductionmentioning
confidence: 99%
“…In DLLME procedure, methanol, ethanol, acetone and acetonitrile are the most common dispersion solvents with volume between 0.5 and 1.5 mL [4,6,8,10]. In our previous research [11][12][13], more than 0.5 mL organic solvent was employed as dispersion solvent. However, in DLLME, the relative large volume of dispersion solvent results in lower enrichment factor (EF) stemed from diminished polarity of aqueous phase by addition of the organic solvent.…”
Section: Introductionmentioning
confidence: 99%